Relation between type and local of orthopedic injuries with physical activity in horses - Nicole Ruas de Sousa (Ciência Rural, 2017)
Equine sport modalities influence the prevalence and predisposition of musculoskeletal injuries in horses. This study aimed to evaluate the prevalence of location and type of orthopedic injuries of horses undergoing various physical activities. Data from 116 horses of different breeds and ages was analyzed. Physical activities included dressage, racing, polo pony, jumping, work and western performance. All horses had history of orthopedic lameness diagnosed by radiographs and/or ultrasound scans. The effect of sport on the affected anatomical site and type of lesion was performed using Fisher’s exact test. Desmitis was more prevalent in animals that performed western sports than in the working ones. The number of fractures was greater in racing and polo pony animals than in working horses. Stifle lesions were more prevalent in dressage horses than working horses and had lower occurrence of shoulder injuries than jumping horses. Hind limb tendon injuries were lower in jumping than in dressage and western horses. We conclude that there is a relationship between location and type of injury and physical activities. In racing horses there is a predominance of young animals and higher prevalence of orthopedic injuries from traumatic events such as tendonitis, desmitis and fractures. In physical activities that require longer training and that animals were used for longer periods, eg. jumping, polo pony, dressage and work, age-related degenerative, such as joint disease, were predominant. In western sport animals the most common lesion was desmitis. Regarding limbs, forelimb injures were more often observed in racing horses, polo pony, jumping and working animals; whereas, dressage and Western sports horses presented more injuries in hind limbs.